2018
DOI: 10.1016/j.ajme.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Is canscore a good indicator of fetal malnutrition in preterm newborn

Abstract: Background: Fetal malnutrition is a risk factor for increased neonatal morbidities and mortalities worldwide. BMI and CANScore had been used for determining fetal malnutrition in term newborns. Objective: To assess the nutritional status of preterm newborns at birth using BMI, PI and CANscore and determine the better indicator for FM. Methods: The study was carried out on consecutive, live-born babies between 28 completed weeks through 36 weeks gestation. Birth weights and lengths were recorded as per protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Even though different experts identified fetal malnutrition at birth by using various assessment methods, clinical assessment of nutritional status (CAN) score, a simple clinical index for identifying the term fetal malnutrition, is a good indicator than other anthropometric approaches [ 5 , 9 , 16 , 17 ]. But for a preterm infant, body mass index (BMI) and ponderal index (PI) are simple and easy tools to use in assessing fetal malnutrition [ 18 ]. Clinical assessment of nutritional status is also important for the prediction of neonatal mortality associated with fetal malnutrition [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though different experts identified fetal malnutrition at birth by using various assessment methods, clinical assessment of nutritional status (CAN) score, a simple clinical index for identifying the term fetal malnutrition, is a good indicator than other anthropometric approaches [ 5 , 9 , 16 , 17 ]. But for a preterm infant, body mass index (BMI) and ponderal index (PI) are simple and easy tools to use in assessing fetal malnutrition [ 18 ]. Clinical assessment of nutritional status is also important for the prediction of neonatal mortality associated with fetal malnutrition [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The nutritional status of reproductive women is one of the determinants of maternal mortality and uneventful pregnancies; however, in 2011 a relatively high ratio (22%) of Senegalese women were below the critical body mass index (BMI) threshold of 18.5 [13]. Many studies have shown that BMI is preferred as an indicator of malnutrition [1517], as it corresponds to a general lack of energy and nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Adebami OJ et al [19] recently reported an incidence of 18.8% of preterm newborns to have FM and significant risk factors for FM included lack of adequate antenatal care, young maternal age (<18yrs), primiparity, maternal undernutrition (BMT<18.5kg/m 2 and MAC<23.5cm), low socio economic status, pregnancy induced hypertension, antepartum hemorrhage and maternal infections especially malaria, urinary tract infections. Prevalence of FM in Preterm neonates (40%) was documented by B.N.Ezenwa [20] and 48.9% as reported by Almarzoki et al [21] from Iraq. It is however, higher than the 26.59 % documented from India by Kamath et al [22] .…”
Section: Discussionmentioning
confidence: 78%